A vascular tissue engineering scaffold with core–shell structured nano-fibers formed by coaxial electrospinning and its biocompatibility evaluation. (20th May 2016) - Duan, Nannan; Geng, Xue; Ye, Lin; Zhang, Aiying; Feng, Zengguo; Guo, Lianrui; Gu, Yongquan
Abstract: In this article, a tubular vascular tissue engineering scaffold with core–shell structured fibers was produced by coaxial electrospinning at an appropriate flow rate ratio between the inner and outer solution. PCL was selected as the core to provide the mechanical property and integrity to the scaffold while collagen was used as the shell to improve the attachment and proliferation of vascular cells due to its excellent biocompatibility. The fine core–shell structured fibers were demonstrated by scanning electron microscope and transmission electron microscope observations. Subsequently, the collagen shell was crosslinked by genipin and further bound with heparin. The crosslinking process was confirmed by the increasing of tensile strength, swelling ratio and thermogravimetric analysis measurements while the surface heparin content was characterized by means of a UV-spectrophotometer and activated partial thromboplastin time tests. Furthermore, the mechanical properties such as stitch strength and bursting pressure of the as-prepared scaffold were measured. Moreover, the biocompatibility of the scaffold was evaluated by cytotoxicity investigation with L929 cells via MTT assay. Endothelial cell adhesion assessments were conducted to reveal the possibility of the formation of an endothelial cell layer on the scaffold surface, while the ability of smooth muscle cell penetration into the scaffold wall was also assessed by confocal laser scanning microscopy. The as-prepared core–shell structured scaffold showed promising potential for use in vascular tissue engineering.